2014
DOI: 10.1007/s10120-014-0387-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of postoperative complications in elderly and oldest old patients with gastric cancer

Abstract: Background The incidence of gastric cancer has been increasing among elderly persons in Japan. This study aimed to clarify risk factors for postoperative complications in oldest old patients with gastric cancer. Methods One-hundred ninety patients more than 75 years old with gastric cancer underwent gastrectomy between 2000 and 2011. Patients were classified into two groups: group A included 29 patients who were 85 years or older (oldest old patients), and group B included 161 patients who were 75-84 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
45
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 35 publications
1
45
1
1
Order By: Relevance
“…These studies also suggested that age alone is not the main factor predicting postoperative outcome. However, previous studies of age‐related differences in gastric cancer surgery were mainly small cohort studies and failed to identify adequate alternative predictors.…”
Section: Introductionmentioning
confidence: 99%
“…These studies also suggested that age alone is not the main factor predicting postoperative outcome. However, previous studies of age‐related differences in gastric cancer surgery were mainly small cohort studies and failed to identify adequate alternative predictors.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality rates for elderly patients undergoing resection for gastric cancer vary considerably in the literature, ranging from 2% to 10.1% in Asian studies and 3% to 8% in European studies 17‐30 . This inconsistency is corroborated by US studies showing 30 days postoperative mortality rates specifically in octogenarians of 5%, 10.2%, and 7.2% using single‐institutional, multi‐institutional, and ACS‐NSQIP data respectively 31‐33 .…”
Section: Introductionmentioning
confidence: 99%
“…This inconsistency is corroborated by US studies showing 30 days postoperative mortality rates specifically in octogenarians of 5%, 10.2%, and 7.2% using single‐institutional, multi‐institutional, and ACS‐NSQIP data respectively 31‐33 . In contrast, these studies have established mortality rates ranging from 0% to 4.1% in their younger patients, with conflicting data on whether or not survival differs between elderly and younger patients 17‐24,26,27‐30,32,33 . Data are similarly conflicting with regards to the outcomes of elderly vs young patients with GE junction tumors undergoing esophagectomy 34‐36 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations